Development of rapid screening method for the diagnostic of fragile x syndrome using real time PCR - Peng, Hoh Boon (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
Fragile X Syndrome (FXS) is the most prevalent inherited cause of mental retardation. The prevalence of FXS in males and females are approximately 1 in 4000 and I in 8000 respectively. It is caused by CGG repeat instability in the FMRl gene, located on chromosome Xq27.3. Normal individuals have CGG repeats ranging from 5 to 53. In premulation carriers, the CGG repeats range from 60 to 200 and shall be more than 200 repeats tor ti.Jil mutation patients. FXS patients have variable clinical features and because of that, an accurate clinical 'diagnosis is always a problem. Currently, Cytogenetic, PCR and Southern Blot Techniques are widely used for diagnosis of FXS. Here we report a pair of brothers suspected to be FXS patients with similar clinical features. However, the cytogenetic result for younger brother did not show fragile site at Xq27.3 of the X chromosome while molecular result was confirmatory for FXS. Conversely, the elder brother showed confirmatory results for Fragile X mutation in both cytogenetic and molecular analysis. We therefore conclude that cytogenetic analysis alone Cftnnot be dependable for the confirmatory diagnosis ofFXS.